An isolated vaginal metastasis from rectal cancer. (February 2016) - Sadatomo, Ai; Koinuma, Koji; Horie, Hisanaga; Lefor, Alan K.; Sata, Naohiro
Abstract: Introduction: Isolated vaginal metastases from colorectal cancer are extremely rare. There are only a few reported cases in the English literature, and the characteristics of such cases of metastasis remain relatively unknown. Presentation of case: We present a case of isolated vaginal metastasis from rectal cancer in a 78-year-old female patient. The patient had no symptoms related to vaginal tumor. Magnetic resonance imaging (MRI) showed thickening of the middle rectum and a vaginal tumor. Biopsy from the vaginal tumor showed adenocarcinoma, similar to the rectal lesion. Low anterior resection with ileostomy, hystero-oophorectomy, and transvaginal tumor resection was performed. After nineteen months, computed tomography scan revealed multiple lung metastases and recurrent tumor in the pelvis. The patient refused chemotherapy and is alive three months after developing recurrent disease. Discussion: Most cases of primary vaginal carcinoma are squamous cell carcinoma. Other histologic types such as adenocarcinoma are usually metastatic lesions. Primary lesions associated with metastatic vaginal adenocarcinoma are most often the uterus, and are very rarely from the colon or rectum. We review previous case reports of isolated vaginal metastases from colorectal cancer and discuss their symptoms, treatments, and outcomes. Conclusion: We should keep the vagina within the field of view of pelvic MRI, which is one of the preoperative diagnostic tools for colorectal cancer. If female patients show gynecological symptoms, gynecological examination should be recommended. Isolated vaginal metastases are an indication for surgical resection, and adjuvant chemotherapy is also recommended. Highlights: Isolated vaginal metastasis from colorectal cancer are extremely rare. Synchronous isolated vaginal metastasis from rectal cancer is reported. To evaluate gynecological symptoms of female patient is important. MRI study is useful to detect and diagnose vaginal lesion.